Desenvolvimento de gerontecnologia educacional tridimensional interativa para prevenção de quedas em idosos - Maia, Juliana Cunha (2020)
The purpose of the study was to develop an interactive educational gerontechnology to prevent falls in the elderly. Descriptive study of the development of model-type gerontechnology, divided into three stages: 1. Development of technology through the Systematic Review of Literature and Situational Diagnosis; 2. Evaluation by judges regarding the objectives, organization, structure, usability, applicability and functionality of the technology; 3. Evaluation by the elderly of appearance, usability, motivational resource and satisfaction, and the Health Promotion Model (MPS) was also used, in which questions related to the components (Characteristics and Individual Experiences and Feelings and Knowledge and Specific Behavior) were used. An analysis of the data occurred by measuring the proportion of agreement of the evaluators (judges and elderly), considering the Agreement Index (CI) greater than or equal to 80%. A characterization of the participants provided descriptive statistics, normality tests, considering a 95% confidence interval for quantitative variables. It was used for data analysis or SPSS version 22.0. Study approved by the Research Ethics Committee of the Federal University of Ceará, with report number 3,614,862. The development of gerontechnology occurred after a systematic review of the literature, which resulted in 11 articles on clinical trials with educational tests for the prevention of falls and situational diagnosis, with 22 elderly participants in an extension group linked to the Federal University of Ceará. Then, create a two-dimensional package by an architect that uses AutoCAD software with distribution of rooms and floors, this basic service for the preparation of the three-dimensional virtual model package through the SketchUp program made up of Prototype 1 (P1). P1 was evaluated by 54 judges, 30 (55.5%) of whom were nurses, 10 (18.5%) of physiotherapists, 6 (11.2%) of architects, 4 (7.4%) of occupational therapists, 3 (5, 5%) doctors and 1 (1.9%) physical educator. Of the 54 judges, 43 (80.0%) were female, 28 (51.8%), 17 (31.4%) practiced assistance practice, 08 (14.8%) were researchers. Of the 38 items selected, all with above-established agreement, with a minimum CI of 88% and a maximum of 100%. As suggestions for modifications, they were listed and activated, constituting Prototype 2 (P2), in the form of a three-dimensional physical model, with a scale of 1:15 elaborated by a model maker. P2 was subjected to an evaluation of 30 elderly participants in the philanthropic institution, with an average age of female, average age of 73.3 years, 22 (73.3%) reported fear of falling, 17 (56.6%) reported having fallen in the last 12 months and 29 (96.6%) that their households presented risks for falls. All items can obtain CI greater than 80%, with a minimum of 83% and a maximum of 100%. As suggestions from the elderly were analyzed and activated, with P2 they underwent changes and resulted in Prototype 3 (P3) final version. The product of this research reveals as an innovative and scientifically grounded tool, however, the use of intervention studies to verify its effectiveness in preventing falls. It is also noteworthy that the positive impact on the demonstration of interactive measures to prevent damage to the home may show health promotion for the elderly and consequently reduce public spending, in addition to allowing the implementation of differentiated practices by nurses and other professionals together. to the elderly population.